Epidemiology of sepsis in Internal Medicine Units of Apulia: results of SEMINA (SEpsis Management in INternal medicine Apulia) study - Belfiore, A.; Mastroianni, F.; Ventrella, F.; Errico, M.; Suppressa, P.; Tomai, M.; Sabatino, S.; De Palma, G.; Pappagallo, F.; Erbi, A.; Simone, O.; Longo, S.; et al. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. The prevalence and mortality of sepsis in Internal Medicine Units (IMUs) is poorly understood as most of the data derive from studies conducted in Intensive Care Units. Aim of SEpsis Management in INternal medicine Apulia (SEMINA) study was to determine the prevalence of sepsis and the characteristics and outcomes of patients with Sepsis-3 criteria admitted in Apulia’s Internal Medicine Units for over six months. Methods. The SEpsis Management in INternal medicine of Apulia study was a prospective, multicentre, observational study. Adult admissions to the 13 Apulia Region’s Internal Medicine Units between November 15, 2018 and May 15, 2019 were screened for sepsis according to the Sepsis-3 criteria. Medical data were collected in electronic case report form. Results. Out of 7,885 adult patients of the Internal Medicine Units, 359 (4.55%) fulfilled the inclusion criteria, and 65 of them (18.1%) met the septic shock criteria. The patients enrolled were elderly, suffering from chronic poly-pathologies and from cognitive and functional impairment. The respiratory system was the most common site of infection and the most common pathogens isolated from blood cultures were Staphylococcus spp., E. coli, Klebsiella spp., Enterococcus spp. and Acinetobacter spp. The in-hospital fatality rate was 31.2% and was significantly higher for septic shock. Sequential Organ Failure Assessment score, dementia and infections from Acinetobacter spp. were independent risk factors for mortality. Conclusions. A high prevalence of sepsis and a high fatality rate were detected in Apulia Region’s Internal Medicine Units. The high fatality rate observed in our study could be related to the underlying diseases and to the vulnerability of elderly patients admitted to our Internal Medicine Units.